2002
DOI: 10.1073/pnas.062478699
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-dependent regulation of intracellular silicon in the aquatic invertebrate Lymnaea stagnalis

Abstract: Silicon is essential for some plants, diatoms, and sponges but, in higher animals, its endogenous regulation has not been demonstrated. Silicate ions may be natural ligands for aluminum and here we show that, in the freshwater snail (Lymnaea stagnalis), intracellular silicon seems specifically up-regulated in response to sublethal aluminum exposure. X-ray microanalysis showed that exposure of snails to low levels of aluminum led to its accumulation in lysosomal granules, accompanied by marked up-regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…36 In complex biological systems, the codeposition of Si and Al is commonly found, and it seems to be an evolutionary mechanism as a protection against aluminum toxicity 37. 38 For example, it has been demonstrated that the pond snail Lymnea stagnalis up‐regulates the internalization of Si when exposed to high concentrations of Al, thus forming a vacuolar lysosomal codeposition of Si and Al 39. In the case of Demospongiae, the spicule‐forming cells, sclerocytes, comprise special vesicles in which the primary stages of spicules proceed.…”
Section: Discussionmentioning
confidence: 99%
“…36 In complex biological systems, the codeposition of Si and Al is commonly found, and it seems to be an evolutionary mechanism as a protection against aluminum toxicity 37. 38 For example, it has been demonstrated that the pond snail Lymnea stagnalis up‐regulates the internalization of Si when exposed to high concentrations of Al, thus forming a vacuolar lysosomal codeposition of Si and Al 39. In the case of Demospongiae, the spicule‐forming cells, sclerocytes, comprise special vesicles in which the primary stages of spicules proceed.…”
Section: Discussionmentioning
confidence: 99%
“…Although aluminum is the third-most abundant element in the Earth's crust (after oxygen and silicon; Weast 1984), its bioavailability is very low due to insoluble hydroxide complexes. Aluminum-stress is answered by plants by excretion of aluminum-complexing compounds as malate or citrate (Kataoka et al 2002, Pineros et al 2002, Tesfaye et al 2001, Ma et al 2001b, Yang et al 2000, Ma, 2000, silicon (Desouky et al 2002), or the synthesis of efflux systems (Sasaki et al 2002). Al(III) becomes toxic under these conditions.…”
Section: 212mentioning
confidence: 99%
“…Insoluble forms of Al are generally considered to be unavailable and therefore less toxic to organisms than the dissolved ion (Al 3 + ) (Driscoll and Schecher, 1989). However, laboratory studies have demonstrated that under near-neutral pH conditions Al can be accumulated in significant amounts by some organisms, in particular filter-feeders (such as bivalves) and grazers (such as snails), causing severe physiological and behaviour disfunction (Elangovan et al, 1997;Kadar et al, 2001;Desouky et al, 2002). Exogenous toxicity has also been demonstrated in fish and crustacea due to precipitation of insoluble Al on the gills (Polé o et al, 1994;Alexopoulos et al, 2003).…”
Section: Introductionmentioning
confidence: 96%